Quantum science in a nutshell: fostering students' functional understanding of models - Ubben, Malte S.; Veith, Joaquin M.; Merzel, Avraham; Bitzenbauer, Philipp (Frontiers in Education, 2023)
Fostering students' understanding of models is a challenge. However, in particular for learning quantum physics an elaborate understanding of models is required. We investigated activities to foster students' functional thinking about (quantum) models in a synchronous online course. The results of an evaluation study (N = 59) showed that the participants improved in their quantum physical thinking about photons and had slightly improved their understanding of physics models in general. A correlation analysis indicates that there are no significant correlations between the students' general understanding of models in physics and their functional understanding of quantum models. Implications of our findings for both teaching and future research with regard to quantum physics education are discussed.